GeVn complexes for silicon-based room-temperature single-atom nanoelectronics. Issue 1 (December 2018) - Achilli, Simona; Manini, Nicola; Onida, Giovanni; Shinada, Takahiro; Tanii, Takashi; Prati, Enrico
Abstract We propose germanium-vacancy complexes (GeV n ) as a viable ingredient to exploit single-atom quantum effects in silicon devices at room temperature. Our predictions, motivated by the high controllability of the location of the defect via accurate single-atom implantation techniques, are based onab-initio Density Functional Theory calculations within a parameterfree screened-dependent hybrid functional scheme, suitable to provide reliable bandstructure energies and defect-state wavefunctions. The resulting defect-related excited states, at variance with those arising from conventional dopants such as phosphorous, turn out to be deep enough to ensure device operation up to room temperature and exhibit a far more localized wavefunction.